Lexical bundles in rhetorical moves in the introduction section of English linguistics research articles from non-Scopus and Scopus journals - Geng, Hui (2024)
The introduction section takes a pivotal role in the construction of a research article (RA). To achieve proficiency in research writing, the building blocks of discourse – lexical bundles and rhetorical moves are indispensable. Lexical bundles are the most frequently occurring sequences of words in a language or register while rhetorical moves are the schematic units that mark textual regularities of research article introductions (RAIs). However, there is limited research on how lexical bundles are used to initiate certain moves to fulfill the discourse-related functions in English RAIs in applied linguistics. Thus, this study aims to fill the gap by identifying the lexical bundles found in rhetorical moves in linguistics RAIs from non-Scopus-indexed and Scopus-indexed journals. For lexical bundle analysis, the quantitative approach was utilized to extract bundles with 3 to 5 words by AntConc 4.2.0 while the qualitative approach was utilized to manually do data refinement and analyze the structural types. For move analysis, the qualitative approach was used for identification of moves and exploration of their sequence and combination while the quantitative approach was used for examining essentiality rates, occurrence frequency, and the relationship between the indexing of journals and the distribution of moves. The corpora comprise 100 English linguistics RAIs, with 50 sourced from two non-Scopus-indexed journals and another 50 from two Scopus-indexed journals. This research adapted two analytical frameworks: Biber et al.’s (1999) structural classification of lexical bundles and Swales’ (1990) Create- A-Research-Space (CARS) model. The results for lexical bundles presented a total of 206 and 253 bundles in moves and steps of RAIs from the non-Scopus and Scopus corpus respectively. As for the structural categories, a total of 13 grammatical structures were detected and the most dominant two types in both corpora were Noun phrase with of-phrase fragment (i.e., the importance of) and (Verb/adjective +) toclause fragment (i.e., are more likely to). The findings for move analysis revealed a new step Move 3 Step 5 (expectation from findings). Meanwhile, the occurrence frequency of Move 3 Step 1B was found to be statistically significantly dependent on the indexing types of journals. Moreover, the most dominant linear type was M1-M2- M3 in both corpora, but there was a difference in the use of the cyclical structure types of moves between the non-Scopus and Scopus corpus. The findings of the combination of moves demonstrated that the percentage of M1+M2+M3 in the Scopus journals is 12% higher than in the non-Scopus dataset. To conclude, this study sheds light on the construction of English linguistics RAIs by connecting lexical bundles with rhetorical moves and investigating the relationship of the indexing of journals with the use of bundles and moves. The outcomes of this study mainly include the generation of a practical list of 3- to 5-word lexical bundles for realizing each move and step and the detection of a new step for the theoretical Swales’ (1990) CARS framework. It would be meaningful for writers to follow the conventions of employing lexical bundles and rhetorical moves in RAIs from Scopusindexed journals with high reputations.